Аленушкины сказки - Мамин-Сибиряк Дмитрий Наркисович (Библиотека школьника, 2018)
Экземпляры: ДБ (20200831) / Инвентарный номер: 52793 / Цена: 120.80 / Сис.шифр: 84(2Роc=Рус) / Авт.знак: Т 51 / ГРНТИ: 17.82.93 / ББК: 84(2Роc=Рус)1